Crystal Growth in Se-Te Chalcogenides: Overview of the Growth/ Relaxation/Viscosity Interplay for Bulk Glasses and Thin Films - Svoboda, Roman; Přikryl, Jan; Provotorov, Pavel; Kolobov, Alexander V; Krbal, Miloš (American Chemical Society, 2023)
Crystal growth in 1 mu m Se(1-y)Tey thin films (for y = 0, 7, 10, and 17) deposited on the Kapton, SiO2 glass, and white glass substrates was researched and quantified by means of a unique combination of direct joint microscopic and calorimetric measurements. As a general feature, the crystal growth in the Se-Te thin films deposited on a Kapton tape was very close to the native/bulk crystal growth. Deposition on the inorganic glassy substrates largely accelerated the crystal growth in the Se-Te thin films due to the build-up of internal tension originating from the large difference in thermal expansion coefficients between the film and the substrate. An additional increase in the crystal growth rate was also caused by the diffusion of Na+ ions from the white glass substrate into the Se-Te films. Almost perfect correspondence was found for the activation energies of crystal growth determined by various measurement techniques (calorimetry and microscopy) and for various Se-Te sample forms (thin films, bulk glass, powdered bulk glass). A very good agreement was found also between the activation energies of viscous flow and structural relaxation at the glass transition temperature Tg. At higher temperatures, the Se-Te thin films exhibit a minor-to-moderate breach of the Stokes-Einstein law, as expressed by the value of Ediger's decoupling parameter xi approximate to 0.80 +/- 0.05. At lower temperatures near the glass transition, the violation of the Stokes-Einstein relation deepens for the thin films with higher Te content. An explanation was proposed based on the potential interconnection between the below-Tg relaxation kinetics and above-Tg connectivity of the undercooled liquid domains (resulting either in changes of the effective hydrodynamic radius during the self-diffusion or in the tendency to create structural inhomogeneities via thermal fluctuations).
Krystalový růst Se-Te chalkogenidů: Přehled vzájemných vztahů mezi růstem, relaxací a viskozitou pro objemová skla a tenké filmy
Keywords: phase-change materials; amorphous selenium; structural relaxation; rearranging regions; optical-properties; crystallization; kinetics; temperature; transition; nucleation; materiály s fázovou změnou; amorfní selen; strukturní relaxace; krystalizační kinetika; nukleace